Dynamics of 2,4-D and Dicamba Applied to Corn Straw and Their Residual Action in Weeds - Gazola, Tiago [UNESP]; Costa, Renato Nunes [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP] (My University, 2022)
2,4-D and dicamba are used in the postemergence management of eudicotyledonous weeds in different crops, most of which are grown under no-tillage systems. Due to the application methods for these products, their dynamics in straw and their residual action in soil have rarely been explored. Thus, the objective of this study was to evaluate the dynamics of 2,4-D and dicamba that have been applied to corn straw and to verify their relationship with residual control action in weeds. In the dynamics experiments, the herbicides were applied to 5 t ha−1 of straw, and rainfall simulations were performed with variable amounts and at different periods after application to evaluate herbicide movement in the straw. In the residual action experiments, the species Digitaria insularis, Conyza spp., Bidens pilosa, Amaranthus hybridus, Euphorbia heterophylla, and Eleusine indica were sown in trays, and 2,4-D and dicamba were applied directly to the soil, to the soil with the subsequent addition of the straw, and to the straw; all of these applications were followed by a simulation of 10 mm of rain. The physical effect of the straw and the efficacy of the herbicides in terms of pre-emergence control of the weed species were evaluated. The leaching of 2,4-D and dicamba from the corn straw increased with a higher volume of rainfall, and the longer the drought period was, the lower the final amount of herbicide that leached. The presence of the corn straw on the soil exerted a physical control effect on Conyza spp.; significantly reduced the infestation of D. insularis, B. pilosa, A. hybridus, and E. indica; and broadened the control spectrum of 2,4-D and dicamba, assisting in its residual action and ensuring high levels of control of the evaluated weeds. In the absence of the straw, 2,4-D effectively controlled the pre-emergence of D. insularis, Conyza spp., and A. hybridus, and dicamba effectively controlled D. insularis, Conyza spp., B. pilosa, A. hybridus, E. heterophylla, and E. indica.
Keywords: auxinic herbicides; choline salt; diglycolamine salt; efficacy; eudicotyledonous; leaching; monocotyledonous